Pentas lanceolata Pentas, Egyptian Starcluster: FPS465/FP465, 6/2007 - Gilman, Edward; Shiffit, Suzanne (EDIS, 2007)
This document provides a detailed overview of Pentas lanceolata, commonly known as pentas or Egyptian starcluster. It describes the plant’s characteristics, including its height, spread, growth rate, and flowering habits. The document highlights the plant’s adaptability to various soil types and its moderate drought tolerance. It also notes the plant’s popularity with butterflies and hummingbirds, and its use in containers, hanging baskets, and as an accent in gardens. Additionally, it covers planting guidelines, maintenance tips, and propagation methods, emphasizing the plant’s suitability for hardiness zones 8B through 11. Original publication date October 1999.